Effect of post-weaning growth rate on carcass traits and meat quality of Nellore cattle - Silva, Luiz H.P.; Paulino, Pedro V.R.; Assis, Gutierrez J.F.; Assis, Debora E.F.; Estrada, Mauricio M.; Silva, Matheus C.; Silva, Jaqueline C.; Martins, Taiane S.; Valadares Filho, Sebastião C.; Paulino, Mário F.; Chizzotti, Mario L. (Meat Science, 2016)
This study evaluated the effects of growth rate during post-weaning growing phase on carcass traits and beef quality. Thirty-four Nellore young bulls were randomly assigned to one of three treatments: LOW, MEDIUM or HIGH growth rate during post-weaning growing phase followed by high growth rate in the finishing phase. The growth rate affected (P < 0.05) all carcass traits evaluated at the end of post-weaning growing phase, except ultimate pH. Carcass dressing was greatest (P < 0.05) for the HIGH growth rate group in both phases. Beef from the HIGH group exhibited the greatest (P < 0.05) sarcomere length and a* and b* colour values at the end of post-weaning growing phase. However, post-weaning growth rate did not affected (P > 0.05) collagen content and solubility, myofibrillar fragmentation index and Warner-Bratzler shear force. Our data suggest that a low post-weaning growth rate produces lighter and leaner carcasses, but it does not affect meat quality traits in Nellore young bulls.
Keywords: Compensatory gain; Meat tenderness; Myofibrillar fragmentation index; Sarcomere length